2021
DOI: 10.52586/5008
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone is a possible new stimulating factor for promoting vascular calcification

Abstract: Introduction 3. Methods 3.1 Animal model preparation 3.2 Experiments 3.3 Data analysis 4. Results 4.1 Noninvasive blood pressure, weight loss, and cardiac weight index of rats 4.2 Von Kossa staining in the aorta 4.3 The calcium content and the activity of ALP in the aorta tissue 4.4 Masson's trichrome staining 4.5 The content of the C-reactive protein, IL-6, TNF-α and MCP-1 in serum 4.6 The content of Urotensin II and aldosterone in the aorta tissue 4.7 The change of the immunoreactivity 5. Discussion 6. Concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In PA patients, aldosterone has been shown to induce vascular wall inflammation, 54 vascular calcification 55 and perivascular fibrosis. 56 Aldosterone also increases early atherosclerosis and promotes plaque formation by activating the MR on smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…In PA patients, aldosterone has been shown to induce vascular wall inflammation, 54 vascular calcification 55 and perivascular fibrosis. 56 Aldosterone also increases early atherosclerosis and promotes plaque formation by activating the MR on smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have shown that vascular calcification is an active process regulated by a variety of molecular signaling pathways ( 4 , 5 , 6 , 7 ), which are highly similar to those involved in bone formation ( 7 , 8 ). Previous studies have shown that TGF-β1 can induce calcification of rat extravascular membrane cells in the calcification medium ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Originally, vascular calcification was considered to be the result of passive degeneration of blood vessels, marking the aging of blood vessels. However, a growing number of studies have shown that vascular calcification is an active process regulated by a variety of molecular signaling pathways ( 4 , 5 , 6 , 7 ), which are highly similar to those involved in bone formation ( 7 , 8 ). Boström et al demonstrated that during calcification, the morphology of rat vascular mesenchymal cells (VSMCs) was altered from the original contractile phenotype to the osteoblast-like phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…CKD patients have a higher risk of developing CVD, and vascular calcification (VC) is one of the strongest predictors of CVD risk [90]. Serum aldosterone levels are increased in CKD patients, and mediate the VC process [91,92]. VC is a highly regulated process in which calcium-phosphate complexes are deposited in the intima and media and participate in ECs, VSMCs, circulating cells and pro-osteogenic and anti-calcifying factors [93,94].…”
Section: Kidney Diseasementioning
confidence: 99%